Popular Law-making : A study of the origin, history, and present tendencies of law-making by statute - Stimson, Frederic Jesup, 1855-1943 (Salt Lake City, UT : Project Gutenberg, 2004)
"Popular Law-making" by Frederic Jesup Stimson is a scholarly exploration of the evolution and significance of legislative processes in the context of English and American law, likely written in the early 20th century. This treatise examines the origins, history, and contemporary trends of law-making by statutes, delving into how law is shaped by legislation as opposed to common law established by judges. The book reflects on constitutional issues and challenges faced by legislators, political parties, and citizens, highlighting the relationship between law-making and societal needs. The opening of the book introduces the author's purpose for the work, which is to elucidate the pressing legislative challenges of the time for a general audience, rather than a legalistic one. Stimson begins by discussing the modern understanding of law as primarily statute law, contrasting it with earlier traditions where law was perceived as a timeless set of customs. He emphasizes the need to understand the roots of law-making and legislative authority, which emerged from early English practices and representative government, setting the stage for the subsequent chapters that will delve into topics such as early English legislation, the Magna Carta, and the evolution of statutory law in both England and America. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by the Online Distributed Proofreading Team from images provided by the Million Book Project
Keywords: Legislation -- United States